The transmission of pottery technology among prehistoric European hunter-gatherers - Dolbunova, Ekaterina; Lucquin, Alexandre; McLaughlin, T Rowan; Bondetti, Manon; Courel, Blandine; Oras, Ester; Piezonka, Henny; Robson, Harry K; Talbot, Helen; Adamczak, Kamil; Andreev, Konstantin; Asheichyk, Vitali; et al. (Nature human behaviour, 2023)
Human history has been shaped by global dispersals of technologies, although understanding of what enabled these processes is limited. Here, we explore the behavioural mechanisms that led to the emergence of pottery among hunter-gatherer communities in Europe during the mid-Holocene. Through radiocarbon dating, we propose this dispersal occurred at a far faster rate than previously thought. Chemical characterization of organic residues shows that European hunter-gatherer pottery had a function structured around regional culinary practices rather than environmental factors. Analysis of the forms, decoration and technological choices suggests that knowledge of pottery spread through a process of cultural transmission. We demonstrate a correlation between the physical properties of pots and how they were used, reflecting social traditions inherited by successive generations of hunter-gatherers. Taken together the evidence supports kinship-driven, super-regional communication networks that existed long before other major innovations such as agriculture, writing, urbanism or metallurgy.
Keywords: Technology; radioaktivní datování; Evropa; zemědělství; Radiometric Dating; Humans; technologie; Europe; Agriculture; lidé